The influence of Dear Me Beauty and KFC co-branding on brand equity and purchase intention - Azzahra, Maghfira Muthia; Bangsawan, Satria (Asian Journal of Economics and Business Management, 2024)
This research investigates the influence of co-branding between Dear Me Beauty and Kentucky Fried Chicken (KFC) on brand equity and consumer purchase intention. The collaboration between a cosmetic brand and a fast-food brand still holds the third position in the unique collaboration category in 2022, indicating the potential to have a significant positive impact on both brands. Using quantitative methods and non-probability sampling, the research findings indicate that the cobranding between Dear Me Beauty and KFC has a positive effect on brand equity and positively influences consumer purchase intention. Additionally, it was found that the brand equity of both brands also has a positive and significant effect on purchase intention. These findings suggest that the collaboration between a cosmetic brand and a fast-food brand can create significant added value for consumers, strengthen their perception of the combined brand, and stimulate the desire to purchase the products offered. In conclusion, the co-branding between Dear Me Beauty and KFC plays an important role in influencing brand equity and consumer purchasing behavior in the current competitive market context.